Climat Policy of the Russian Federation and the Problem of Global Climate Change - Juliya A. Rusakova (Vestnik MGIMO-Universiteta, 2015)
The article considers the participation of Russia in the system of global governance of climate change. Object of analysis is the Climate Doctrine of the Russian Federation. Climate Doctrine states that global warming may have both a negative and positive consequences for our country in view of its geographical position, length and area. These features, as well as the low population density in the regions of greatest climate risk, open up additional opportunities for adaptation to climate change. At the same time it emphasizes the need to prevent conflict of regional interests in the formation of climate policy. The author advocates a more active position of Russia in overcoming the effects of climate change, as well as the reduction of anthropogenic impact on the global climate effects. It emphasizes the role of civil society and the media in the development of environmental awareness among the political elite of the country. The article separately considers Moscow's participation in the formulation and implementation of climate policy in Russia. Currently, the Department of Natural Resources and Environmental Protection of Moscow is working on updating the Memorandum of Understanding between Moscow and C40 (Partnership of major cities in the fight against climate change) as the main framework document regulating cooperation with the C40 and the membership of Moscow in the organization.